Enhancing user interaction through the design of digital information environments in information services - Borysenko, Olha; Diachenko, Mariia; Diachenko, Iryna; Kravchenko, Oleh; Shunevych, Yevheniia (Sustainable Engineering and Innovation, 2026)
The interface computer systems are adaptive and context-aware in order to enhance user engagement in online information environments, such as Ukrainian digital services, such as Diia, and library systems based on VuFind. The discovery of the usability perceptions, critical design aspects, and cultural influences is conducted through a qualitative thematic analysis through an analytical sample and in-depth interviews with 10-20 users of digital platforms in Ukraine. The study proposes a context-aware UX framework (CAUXF), which has adaptive interface design, environmental, behavioural, and cognitive-emotional characteristics, and user modelling with personalisation. The proposed model consists of a user context profile, a context information manager, a conversation supervisor, a context-awareness service manager, and embedded mobile services. The researchers concluded that 45% of digital platform users in Ukraine rated them as being moderately challenging to use, half of them recognised key elements of design such as simplified user interfaces, and 60% desired the capability to customise it. The cultural and contextual analysis of the Ukrainian-language interfaces in the current study revealed that 80% of them were preferred. The paper highlights the relevance of user-centred design considerations that meet the needs of Ukrainian digital users in their technological and cultural contextual environment by using more simplified interfaces, mobile compatibility, language localisation, and infrastructure issues.